BRIEF CONSIDERATIONS REGARDING THE SUPREMACY OF THE UNION REGULATION IN RELATION TO NATIONAL ACTS - VÂLCU , Elise-Nicoleta (International Journal of Legal and Social Order, 2022)
The European Union is an international integration organization in the sense that we constantly retain requests from some European states for accession. The EU is not an international organization in the classical sense, departing significantly from the terminology established by international law. So, we are in the presence of an autonomous governance, with individual rights and powers. In this sense, the member states have given up part of their legislative sovereignty in favour of the Union in order to jointly exercise the prerogatives deriving from this transfer. Also, the European Union is based on sources of law that give rise to a legal system distinct from the systems of the member states, characterized by its supremacy in relation to the latter. The present study aims to address the issue of the supremacy of the Union law system, in relation to the national law, with special reference to the supremacy of the main source derived from the Union, the regulation, in relation to the sources of the national legal order.